Criminal Responsibility of Underage Drivers Causing Death from the Perspective of Positive Law and Islamic Criminal Law - Hasibuan, Farhan El Miftah; Muchsin, Abdul (LEGAL BRIEF, 2025)
This research aims to examine the issue of minors driving motor vehicles resulting in death, through two distinct legal perspectives: Islamic Criminal Law and Positive Law. The study specifically focuses on understanding the criminal responsibility of minors under both frameworks, highlighting the contrasting approaches in determining age limits for criminal liability. In Islamic Criminal Law, minors under the age of 15 or 18 are considered not fully responsible, whereas Positive Law holds individuals under the age of 18 and unmarried accountable. This research explores the legal implications of this discrepancy and the phenomenon of minors being accused and detained in legal cases. Additionally, the study addresses the distinction between Positive Law, which operates as a vertical relationship with the state, and Islamic Criminal Law, which represents a horizontal relationship with accountability to Allah. The aim is to analyze how Islamic Criminal Law, often criticized as inhumane or outdated by some, contrasts with the more state-centric Positive Law, especially in a multi-religious and diverse country like Indonesia. The research adopts a normative-empirical legal approach, combining both theoretical legal analysis and empirical investigation to explore these perspectives on criminal responsibility